PERSEPSI PELAKU HUTAN RAKYAT DAN INDUSTRI KAYU SKALA KECIL-MENENGAH TERHADAP KESIAPAN IMPLEMENTASI SVLK - Elvida Yosefi Suryandari; Deden Djaenudin; Iis Alviya (Jurnal Analisis Kebijakan Kehutanan, 2017)
Indonesian forestry authority has established Timber Legality Verification System called SVLK as a mandatory basis. The progress of implementation of SVLK certification for large-scale forestry enterprises has been done considerable, but for the small-scale industry (IKM) and private forest (HR) have difficulty to meet the SVLK standard. This paper aims to determine the entrepreneurs’ perception on the factors that could improve the readiness of industries and private forest enterprises in the implementation of  SVLK. Descriptive analysis and likert scalescoring methods were used in the study, based on economic and institutional aspect. This research was carried out in three locations, in DKI Jakarta, DI Yogyakarta and West Java Province. The achievement of SVLK implementation based on the number of SVLK is still low. According perception of the small-medium enterprises and private forests, they  have not ready yet to implement SVLK. In economic aspects, access to markets and rising output prices are the factors that make the entrepreneurs ready. Meanwhile, in institutional aspect, efficient certification procedural; local government support in the licensing process; increase of understanding and awareness about SVLK and coordination among stakeholders are required. Ideal institutional forms such as check-off program (association or cooperation) as one of the best solutions to improve SVLK implementation.